Meios de comunicação utilizados e seus reflexos na adoção de tecnologias por integrantes da cadeia produtiva de arroz no Mato Grosso - Hélio Augusto de Magalhães (Revista IDEAS, 2011)
The purpose of this article is the presentation of some media, which are used by the different segments of the rice production chain, in Mato Grosso, Midwest region of Brazil. The article proposes to observe the information flow between producers, associations, rural extension and the other members of this chain. The article describes concepts and practices of communication, from the perspective of the relationship, and the importance of communication research as a fundamental point for social interaction and generation of technological knowledge. The survey results illustrated successfully this technique for field research. This study showed that the relationship between actors of some determinated productive chain allows evaluating the communicative participation way of each agent in the scenario